The peril in ignoring the Protocols - Henry, Marilyn (Judaism, 2006)
If, however, The Protocols are genuine (which can never be proven conclusively), it might cause some of us to keep a wary eye on world affairs.2 For its part, Amazon.com, which classifies the book as "controversial knowledge" (apparently along with books on UFOs, demonic possession and "all manner of conspiracy theories"), also uses this as a marketing opportunity for books that expose the Protocols. An authority on human rights, a former Israeli representative at the United Nations and a veteran Israeli judge, Ben-Itto retired from the judicial life to research and write an authoritative account of the life the Protocols.